EFL STUDENTS’ PREFERENCES FOR CORRECTIVE FEEDBACK IN SPEAKING INSTRUCTION ACROSS SPEAKING COURSE LEVELS - Nurul Atma; Utami Widiati (Bahasa dan Seni: Jurnal Bahasa, Sastra, Seni, dan Pengajarannya, 2015)
This cross-sectional survey study investigates the preferences of freshmen and sophomores for corrective feedback in speaking instruction, which includes perception of corrective feedback, types of error to be corrected, timing of correction, sources of correction, and types of corrective feedback. Using questionnaire and interview to collect the data, the study found that the two groups welcomed the feedback, acknowledged the benefits of corrective feedback, but felt embarrassed when being orally corrected. Both the freshmen and sophomores wanted all their errors to be corrected. Whereas the freshmen preferred the grammatical errors to be always corrected, the sophomores preferred the phonological errors. With regard to the timing, the two groups expected their errors to be corrected after they finished speaking. Additionally, the two groups favored teacher feedback. Finally, regardless of the different types of errors, the most preferred feedback was explicit feedback, whereas the least preferred one was paralinguistic signal.